Synthesis and physicochemical properties of pyrazole containing xanthine derivatives - Aleksandrova, K. V.; Levich, S. V.; Mikhalchenko, E. K.; Bilyaev, M. O.; Александрова, Катерина Вячеславівна; Левіч, Сергій Вадимович; Михальченко, Євген Костянтинович; Біляєв, М. О. (К.: Національний університет харчових технологій, 2016)
Heterocycle containing compounds (xanthines, pyrazoles, thiazoles etc) represent very important structural units in drug discovery. A survey of literature reveals the biological properties of these substances including hypoglycemic, anticancer, antioxidant, anti–inflammatory, bronchodilator andxanthine oxidase inhibitory effects [1–3]. In our opinion, combination of several heterocyclic systems in one molecule could improve pharmacological properties. Aim of our work was a development of method of thiazole and triazole containing xanthine derivativesynthesis.